A Critical Discourse Analysis of The Representation of Resistance In A. A. Navi's Short Story "Robohnya Surau Kami" - Nursanti, Cita Afiyah; Djuharie, Otong Setiawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research investigates the theme of resistance in A. A. Navis’s short story Robohnya Surau Kami (The Collapse of Our Surau) via Norman Fairclough’s Critical Discourse Analysis (CDA) approach. Initially published in 1956, this narrative is regarded as one of the pivotal pieces in Indonesian literature due to its commentary on religious formalism, societal fatalism, and apathy towards social inequities. Utilizing a qualitative descriptive technique, this study treats the text of the story as its main data and examines it through Fairclough’s tripartite model: micro (textual examination), meso (discursive practice), and macro (sociocultural context). The results illustrate that on the micro level, Navis employs emotionally charged language, irony, satire, and repetition to contest limited understandings of faith and highlight social accountability as an ethical duty. On the meso level, the complex narrative structure and the employment of traditional Minangkabau storytelling methods serve as discursive techniques to express criticism in a subtle yet effective manner. Characters like Ajo Sidi and the Grandfather embody conflicting ideological viewpoints that shape the conversation around resistance. At the macro level, the narrative mirrors the socio-historical realities of Indonesia in the post-independence era, specifically addressing challenges such as structural poverty, religious formalism, and cultural fatalism. The research concludes that Robohnya Surau Kami is a significant example of ideological resistance, promoting a harmony between spiritual commitment and active societal involvement. These outcomes add to the increasing utilization of CDA in literary analysis and confirm the lasting significance of Navis’s work as a medium for social critique and ideological contemplation.